2022
DOI: 10.3390/applbiosci1020012
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inoculation with Phosphate-Solubilizing Microorganisms of Rock Phosphate and Phosphogypsum and Their Effect on Growth Promotion and Nutrient Uptake by Ryegrass

Abstract: In the previous half-century, natural rock phosphates (PN) have been a valuable alternative for phosphorus (P) fertilizer for sustainable agriculture; furthermore, phosphogypsum (PG) has been widely used as a soil amendment fertilizer since it improves some soil properties, increases crop yields, and represents an environmental concern that can make a good economic profit; this research aimed to study the effects of microbial consortia of phosphate-solubilizing microorganisms (PSM) on the solubilization of PN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
2
5
0
Order By: Relevance
“…The greatest increase in the P removal from the biologized fertilizer and its conversion into a form available for plants was observed for V5 treated with the apatite concentrate of standard grinding in combination with strains BI2, BI14, and BS89 (4 × 10 6 CFU/g each) and for V8 treated with the apatite concentrate of fine grinding in combination with strains BI14 and BS89 (6 × 10 6 CFU/g each). This result is in accordance with the previous study [19] of the effects on ryegrass of co-inoculation Pseudomonas fluorescens (MW165744) with apatite, which represented the significant increase of total P uptake. It can be assumed that analogous results of these two experiments reflect the similarity of experimental methods for analyzing the growth of Lolium multiflorum in sterilized soil conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The greatest increase in the P removal from the biologized fertilizer and its conversion into a form available for plants was observed for V5 treated with the apatite concentrate of standard grinding in combination with strains BI2, BI14, and BS89 (4 × 10 6 CFU/g each) and for V8 treated with the apatite concentrate of fine grinding in combination with strains BI14 and BS89 (6 × 10 6 CFU/g each). This result is in accordance with the previous study [19] of the effects on ryegrass of co-inoculation Pseudomonas fluorescens (MW165744) with apatite, which represented the significant increase of total P uptake. It can be assumed that analogous results of these two experiments reflect the similarity of experimental methods for analyzing the growth of Lolium multiflorum in sterilized soil conditions.…”
Section: Discussionsupporting
confidence: 93%
“…However, the best performance was observed for V5 (13.09%), which appeared to have optimal parameters in terms of the grinding degree and combination and amount of PSMs. Our results on PUE, which was calculated considering the direct effect of P on ryegrass, are consistent with those obtained in one-and two-year field experiments at Rothamsted (UK), where the average P recovery calculated by a different method was 5-10% [19,24].…”
Section: Discussionsupporting
confidence: 90%
“…PSMs are known to promote plant growth. The study of Amri et al [ 47 ] showed results related to this. The results of our study were also consistent with this observation.…”
Section: Discussionmentioning
confidence: 77%
“…These organic acids help reduce soil pH and may act as chelators for divalent cations such as calcium, releasing bonded phosphorus iron for plant absorption (Saxena et al, 2019 ). For instance, Amri et al ( 2022 ) found that using Pseudomonas fluorescens as a P-fertilizer on ryegrass increased root proliferation and plant biomass. This approach is promising and could serve as an alternative source of P-fertilizers to maintain high nutrient levels in crops such as maize, wheat, and rice (de Abreu et al, 2017 ; Li et al, 2021 ).…”
Section: Mineral Solubilizersmentioning
confidence: 99%